SELF-CONFIDENCE REFLECTION: A QUR'`ANI COUNSELING PERSPECTIVE - Imalatul Khairat; Rini Fitriani Permatasari; Eni Nur'aeni; Sarni Sarni; Triave Nuzila Zahri (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2024)
Self-confidence is the ability of individuals to face new problems or challenges by optimizing their development, so the lack of self-confidence experienced by individuals cannot be considered a common issue. Confidence issues can impact an individual's success in achieving future goals. This article presents the results of the author's literature review on studies of self-confidence that can be enhanced through the application of Qur'anic counseling. The author examines approximately six studies on self-confidence and Qur'anic counseling. Counseling from the perspective of the Qur'an is highly relevant to serve as a pillar of life and a fundamental basis for Muslims in seeking answers to various evolving issues. The conclusion of this article reveals that individuals who understand the meaning of the Qur'an will have self-confidence because they make the Qur'an a philosophy of life.